2011
DOI: 10.1002/asia.201100455
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Applications of Tricarbonyliron Complexes of Dendralenes

Abstract: [3]Dendralene and [4]dendralene are converted smoothly into tricarbonyliron complexes. The structures of four complexes analyzed by DFT and single-crystal X-ray analysis show that, in contrast to free hydrocarbons, complexed dendralenes prefer a roughly in-plane conformation. The complexes are stable towards Fe(CO)(3) group migration up to 150 °C. The synthetic value of Fe(CO)(3) complexation in the dendralene series is demonstrated through a variety of selective synthetic manipulations (Diels-Alder reaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…Building on an important early study on the {Fe(CO) 3 } complexes of [4]dendralene (21) by Greene et al, [236] Sherburn and co-workers demonstrated that the tricarbonyliron complexes of [3]-and [4]dendralene can be readily prepared in good yield on a multigram scale through an azabutadienecatalyzed reaction of [Fe 2 (CO) 9 ] with the parent hydrocarbon 11 (Scheme 74). [237] The structures, properties, and reactions of these complexes were studied through a joint computational/experimental approach with Paddon-Row and coworkers. This study demonstrated the utility of these complexes in the formation of products that cannot be accessed directly from the dendralenes, including unprecedented hybrid linear/branched conjugated hydrocarbon 372.…”
Section: Methodsmentioning
confidence: 99%
“…Building on an important early study on the {Fe(CO) 3 } complexes of [4]dendralene (21) by Greene et al, [236] Sherburn and co-workers demonstrated that the tricarbonyliron complexes of [3]-and [4]dendralene can be readily prepared in good yield on a multigram scale through an azabutadienecatalyzed reaction of [Fe 2 (CO) 9 ] with the parent hydrocarbon 11 (Scheme 74). [237] The structures, properties, and reactions of these complexes were studied through a joint computational/experimental approach with Paddon-Row and coworkers. This study demonstrated the utility of these complexes in the formation of products that cannot be accessed directly from the dendralenes, including unprecedented hybrid linear/branched conjugated hydrocarbon 372.…”
Section: Methodsmentioning
confidence: 99%
“…B. 11 ) hergestellt werden können (Schema ) 237. Die Strukturen, Eigenschaften und Reaktionen dieser Komplexe wurden in einer experimentell/theoretischen Studie in Zusammenarbeit mit der Arbeitsgruppe Paddon‐Row untersucht.…”
Section: Weitere Reaktionen Der Dendraleneunclassified
“…We recently demonstrated that 12, the iron tricarbonyl complex of the parent [3]dendralene, undergoes cross metathesis with various olefins to gave stable, isolable complexes of 1E-substituted [3]dendralenes 13 (Scheme 2). 16 This work was extended to complexes 13a-e, carrying aryl, alkyl and ester substituents. Gratifyingly, oxidative decomplexation 17 was sufficiently rapid at 0 1C to generate, after workup, CDCl 3 solutions of 1E-aryl, alkyl and carboethoxy-substituted [3]dendralenes 8a-e that were free of DA dimerisation products and other contaminants, as shown by NMR spectroscopic analysis.…”
Section: Communicationmentioning
confidence: 99%